Research Priorities in Speech Pathology / Therapy in Pakistan: A Cross Sectional Survey (Medical Forum Monthly, 2021)
Objective: To find out Research priorities in Speech Pathology /Therapy, Lahore Pakistan.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of health Professional Technologies, the University of Lahore from January 2016 to July 2016.Materials and Methods: Convenient sampling technique was use. The Sample Size 270 Generated by Saunders on the bases of total population. Closed ended questions have been developed from literature review and expert opining, and distributed to around 300 participants. Questionnaires were distributed among HODs, teachers and students. Part A and B. Part A of questionnaire contained personal information, part B is about research activities in Institution.Results: Most of the respondents were between age 25 to 30 years. 86.75 % SLPs are female and only 13.35% are male. Most of the participants having Master 100(37%), only 5(1.9%) participants were Ph.D degree holder. About 58% to 94% of participants were responded that they have no published article in national, international journal and there was no journal prescription of institute. P value was less than 0.05 in responses of teachers and students.Conclusion: Research concludes that most of participants have no journal prescriptions and they were not publishing article. It is dire need to promote research culture in speech pathology department.